2023
DOI: 10.1186/s40359-023-01162-x
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality and homelessness: prevalence and associated factors of suicidal behaviour among homeless young adults in Southern Ethiopia

Abstract: Background Research indicates that homelessness is associated with an increased risk of suicide. While street homelessness is a global problem, it is a disproportionately serious concern in low- and middle-income countries such as Ethiopia. Despite their high risk of suicidal thoughts and attempts, there has been limited research on this subject among homeless young people in Ethiopia. Therefore, we assessed the prevalence and factors contributing to suicidal behaviour among homeless young peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Among associated factors of suicidal behavior, living alone makes respondents 2.53 times more likely to have suicidal behavior than respondents who live with family. This might be due to the fact that those who lived alone had no nearby family with whom they could communicate and share their problems, which could lead to increased hopelessness and suicidal behavior among people who live alone ( 56 ), which is supported by a study conducted in the South Gondar zone, Northwest Ethiopia ( 57 ) and residents in Northwest Ethiopia ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among associated factors of suicidal behavior, living alone makes respondents 2.53 times more likely to have suicidal behavior than respondents who live with family. This might be due to the fact that those who lived alone had no nearby family with whom they could communicate and share their problems, which could lead to increased hopelessness and suicidal behavior among people who live alone ( 56 ), which is supported by a study conducted in the South Gondar zone, Northwest Ethiopia ( 57 ) and residents in Northwest Ethiopia ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of adult samples with risk factors for poor mental health tended to report levels of suicidal ideation greater than the prevalence rate found in this study (21.1%). For instance, a study of adult outpatients with epilepsy in northwest Ethiopia found a 26.5% rate of suicidal ideation (Nigussie et al, 2021), while 38.2% of homeless adults in southern Ethiopia reported suicidal ideation (Yohannes et al, 2023). More recent systematic reviews and meta‐analyses have continued to report elevated levels of suicidal ideation, with one reporting a 12.1% pooled prevalence rate of suicidal ideation (Farooq et al, 2021) and another reporting a significant increase in suicidal ideation and attempts in both clinical and non‐clinical samples (Yan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%